The reception of Walter Pater in Europe - Bann, Stephen (Athlone critical traditions series ;, 2004)
Just over a century after his death, Walter Pater''s critical reputation now stands as high as it has ever been. In the English-speaking world, this has involved recovery from the widespread neglect and indifference which attended his work in the first half of the twentieth century. In Europe, however, enthusiastic disciples such as Hugo von Hofmannsthal in the German-speaking world and Charles Du Bos in France, helped to fuel a growing awareness of his writings as central to the emergence of modernist literature. Translations of works like Imaginary Portraits, established his distinctive voic.